2014
DOI: 10.3389/fgene.2014.00312
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression responses of threespine stickleback to salinity: implications for salt-sensitive hypertension

Abstract: Despite recent success with genome-wide association studies (GWAS), identifying hypertension (HTN)-susceptibility loci in the general population remains difficult. Here, we present a novel strategy to address this challenge by studying salinity adaptation in the threespine stickleback, a fish species with diverse salt-handling ecotypes. We acclimated native freshwater (FW) and anadromous saltwater (SW) threespine sticklebacks to fresh, brackish, and sea water for 30 days, and applied RNA sequencing to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 63 publications
0
40
2
Order By: Relevance
“…Active ion transport across plasma membranes; expressed in both gill and kidney tissues during osmoregulation (Perry et al, 2003;Wang et al, 2014). Outlier between freshwater and marine stickleback populations (DeFaveri et al, 2011;Shimada et al, 2011).…”
Section: Atp1a1mentioning
confidence: 99%
See 3 more Smart Citations
“…Active ion transport across plasma membranes; expressed in both gill and kidney tissues during osmoregulation (Perry et al, 2003;Wang et al, 2014). Outlier between freshwater and marine stickleback populations (DeFaveri et al, 2011;Shimada et al, 2011).…”
Section: Atp1a1mentioning
confidence: 99%
“…Freshwater osmoregulation -dilution of urine to conserve ions; expressed in kidney tubules (Kato et al, 2011;Wang et al, 2014).…”
Section: Nkcc2mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cytochrome P450 (CYP) 1A1 gene has not been studied extensively, and the results so far are confusing (Aldawsari et al, 2014;Wohak et al, 2014). Several studies (Lee et al, 2010;Arinc et al, 2014;Henderson et al, 2014;Wang et al, 2014;Gaspar-Ramirez et al, 2015) have shown that patients with CYP1A1 deletion cannot produce the active enzyme, so that carcinogenic substances cannot be metabolized and excreted. The long-term presence of carcinogenic substances coupled with smoking increased the susceptibility to lung cancer.…”
Section: Introductionmentioning
confidence: 99%